Pengaruh Produktivitas Tenaga Kerja, Pendidikan, dan PDRB Per Kapita Terhadap Kemiskinan di Provinsi Bali - Pratiwi, Seruni; Sutrisna, Ketut (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol. 3, No. 10, Oktober 2014 (pp.431 - 484), 2014)
Poverty remains a serious problem that seized the attention of the local government of Bali Province. The government  of Bali Province even set poverty reduction as the top priority in their development goal plan. This study aims to find out the relationship of labor productivity, education that is proxied by mean years school (MYS), and GDRP per capita on poverty using multiple linear regression and also equipped by Vector Autoregression (VAR) test. The results state that GDRP per capita can not be included into the regression model because it contains the highest multicollinearity, so it should be excluded from the model. However, based on the results of granger causality test in VAR analysis states that the variable of GDRP per capita affects poverty. The results of this study also show that education negatively effect the poverty in the Province of Bali in 1996-2012, while labor productivity has no significant effect.
Keywords: poverty , labor productivity , education , GDRP per capita